The Relationship Between Knowledge and Working Mother for Breastfeeding in Sidomulyo, Stabat - Fitri, Rahmi; Panjaitan, Nurhikmah (Talenta Publisher, 2020)
Breast milk contains substance known as IgA for the defense system in digestive tract against infection. This study aims to determine the relationship between knowledge and working mothers with exclusive breastfeeding in Sidomulyo, Stabat. The type of research used is a descriptive analytic survey using a cross sectional study. The sampling technique used accidental sampling with 150 as population and 30 people is involved as the research sample. The data analysis applied chi square test to determine the relationship between two variables. The results of this study revealed that there is a relationship between mother's knowledge of exclusive breast feeding with a significant level (ɑ) = 5% (0.05) and df = 2, the result is value = 0.026 at df = 2 where sig <ɑ (0.026 < 0.05) then Ho is rejected and Ha is accepted. Therefore, mothers are advised to continue to provide exclusive breastfeeding to their babies even though they work by storing breast milk in the refrigerator.